Pengaruh Isolat Bakteri Asam Laktat dari Feses Pedet Sapi Perah Baru Lahir Terhadap Produksi Asam Laktat dan Perubahan pH pada Ampas Tahu - Ismail Jasin; Zaenal Bachrudin (Agricultural Faculty, 2013)
The effect of lactic acid bacteria (LAB) isolate culture from young calves feces on the lactic acid production and ph tofu wasteABSTRACT. The objective of this study was to study the effect of isolated lactic acid bacteria (BAL) addition on lactic acid production and pH of tofu waste and for improving the expired tofu waste industry. Inoculum from liquid media as starter was applied anaerobically for 0%; 5% and 10% and different incubation time were 0; 3; 6; 12; 24; 48 and 72 hours. Variabel measure in this study were lactic acid production and pH. The different level addition level of inoculum percentage applied in tofu waste improve expired date of tofu waste industry, and incubation time very significantly increase lactic acid production (P0.01). As a conclusion of this study showed that 10% of inoculum and 24 hours incubation perform an optimum of tofu waste industry fermentation.